Effects of Age on Emotion Regulation, Emotional Empathy, and Prosocial Behavior. (17th July 2018) - Bailey, Phoebe E; Brady, Brooke; Ebner, Natalie C; Ruffman, Ted
Abstract: Objectives: The degree to which older adults experience emotional empathy and show subsequent prosocial behavior versus experience personal distress in response to another's distress remains unclear. Method: Young ( n = 40; 17–29 years) and older ( n = 39; 61–82 years) adults watched videos of individuals expressing pain or no pain. Pain mimicry was recorded using facial electromyography. Participants were then asked if they would spend the remaining time helping the experimenter. Self-reported tendency to suppress or reappraise emotion was assessed, as well as trait and state emotional empathy and personal distress. Results: Pain mimicry was associated with reduced trait suppression in older adults. In both age groups, greater emotional empathy, averaged across video condition, was associated with increased helping. In addition, relative to young adults, older adults reported more personal distress and emotional reactivity in response to the videos but were just as willing to help. They also put more effort into helping. Discussion: These findings contribute to clarification of mixed previous evidence regarding the experience of emotional empathy in young versus older adulthood. We discuss the importance of considering additional subcomponents of empathy such as emotion regulation, while also accounting for the relevance of the empathy induction to each age group.